The Global Race for Talent: Brain Drain, Knowledge Transfer, and Growth - Marta Prato (The Quarterly Journal of Economics, 2025)
Abstract How does inventors’ migration affect international talent allocation, knowledge diffusion, and productivity growth? To answer this question, I build a novel two-country innovation-led endogenous growth model, where heterogeneous inventors produce innovations, learn from others, and make dynamic migration and return decisions. Migrants interact with individuals at origin and destination, diffusing knowledge within and across countries. To quantify this framework, I construct a micro-level data set of migrant inventors on the U.S.-EU corridor from patent data and document that (i) gross migration is asymmetric, with brain drain (net emigration) from the EU to the United States; (ii) migrants increase their patenting by 33% a year after migration; (iii) migrants continue working with inventors at origin after moving, although less frequently; (iv) migrants’ productivity gains spill over to their collaborators at origin, who increase patenting by 16% a year when a co-inventor emigrates. I calibrate the model to match the empirical results and study the effect of innovation and migration policy. A tax cut for foreigners and return migrants in the EU that eliminates the brain drain increases EU innovation but lowers U.S. innovation and knowledge spillovers. The former effect dominates in the first 25 years, increasing EU productivity growth by 3%, but the latter dominates in the long run, lowering growth by 3%. On the migration policy side, doubling the size of the U.S. H1B visa program increases U.S. and EU growth by 4% in the long run, because it sorts inventors to where they produce more innovations and knowledge spillovers.